Releasing Nanocapsules for High‐Throughput Printing of Stable Perovskite Solar Cells. Issue 34 (16th July 2021) - Huang, Zengqi; Hu, Xiaotian; Zhao, Zhipeng; Meng, Xiangchuan; Su, Meng; Xue, Tangyue; Chi, Jimei; Xie, Hongfei; Cai, Zheren; Chen, Yiwang; Li, Lin; Song, Yanlin
Abstract: Perovskite solar cells (PSCs) are promising photovoltaic technologies due to their impressive power conversion efficiency (PCE) and low‐temperature fabrication process, while it is still challenging to print uniform perovskite film with high crystalline quality over a module size. Here, a printable and stable perovskite nanocapsules ink to realize the high‐throughput printing of large‐area, highly uniform perovskite films with micron grain size is reported. It is discovered that the releasing effect of these perovskite nanocapsules promotes homogeneous nucleation by diffusion‐controlled growth due to the steady‐state diffusion of the solute in solution. Remarkably, the printed PSCs and 25 cm 2 modules achieve power conversion efficiencies of 22.10% and 16.12%, respectively. They exhibit negligible efficiency loss after continuous operation for over 1000 h under AM1.5 illumination, and excellent thermal (85 °C) stability with over 87% of the initial efficiency after aging for 500 h. This perovskite nanocapsules ink is expected to facilitate the high‐yield fabrication of perovskite photovoltaics. Abstract : A novel type of releasing nanocapsule is designed and demonstrated for high‐throughput printing of highly efficient perovskite solar cells with excellent stability. The releasing effect of these perovskite nanocapsules promotes homogeneous nucleation by diffusion‐controlled growth. A record manufacturing efficiency of 140 s is demonstrated for perovskite solar modules installation of 1 kW.